Konsumsi Kurma Ajwa Dan Madu Akasia Untuk Peningkatan Kadar Haemoglobin Remaja Putri Di Pondok Pesantren Nurul Anwar Komba Sentani - Suryati Romauli; Heni Voni Rerey; Roganda Simanjuntak; Widia Yulia Ningrum (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Anemia remains a nutritional problem, especially for adolescent girls. This is due to the fact that many girls ignore risk factors. Anemic adolescents may be less productive at work or perform poorly in school due to a lack of motivation and focus. This community service project aims to raise awareness among adolescent girls about anemia and its management by providing access to ajwa dates and acacia honey. The activity's methodology includes educating adolescent girls about anemia through leaflets, followed by a hemoglobin level check (pre-test), administering ajwa dates and acacia honey to adolescent girls with anemia at the Nurul Anwar Komba Sentani Islamic Boarding School, and re-checking their hemoglobin levels (post-test). Anemic adolescent girls who received ajwa dates and acacia honey every morning and evening for 14 days experienced increased hemoglobin levels as a result of this community service.